KESEHATAN REPRODUKSI: RUANG LINGKUP DAN KOMPLEKSITAS MASALAH - Muhadjir Darwin (Populasi, 1996)
Reproductive health covers a number of elements that relates to sexual activities and reproductive processes. The clinical aspects of the reproductive health are indeed important. Yet, its social aspects are not less significant due to its complexity and difficulty for making a solution. Many social problems associated with reproductive health, such as unwanted pregnancy, unsafe abortion, STD/AIDS, side-effects of contraceptive uses, etc., have grown to be more crucial and call for serious attention from social scientists as well as policy makers. This paper specifically addresses this issue by elaborating the scope and complexity of reproductive health matters in an Indonesian context.